(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
The Multichannel Analysis of Surface Waves (MASW) is an effective method for near-surface analysis. The method was employed at the Ahmadu Bello University, Zaria (Phase II site) to determine the shear wave velocity of the site. The dispersive characteristics of Rayleigh type of the surface waves was used to infer the shear wave velocity of the site down to 30 m (Vs30). The average Vs30 obtained of the site varies between 236.6 m/s to 294.5 m/s. Therefore, the soil of the site is stiff